Análisis de la demanda de usuarios, en la determinación de paraderos tipo. caso: “zonas de espera del SITP – Bogotá” (2021)
This work presents the proposal for the optimization in the design of the stop zones “Paraderos” for the Integrated Transportation System “SITP” of the city of Bogotá, in order to generate a method for sizing them, in a way that through the calculation of the demand of users of the whereabouts, of the level of service desired and of the urban characteristics; A type of whereabouts can be established, according to the location and refuge rates. The study was based on the information of the whereabouts of the city of Bogotá and the demand of users of the SITP, in the way of work, on the characteristics of the M10 whereabouts.